2013
DOI: 10.18553/jmcp.2013.19.9.755
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Economic and Humanistic Burden of Illness in Irritable Bowel Syndrome and Chronic Constipation

Abstract: BACKGROUND: Irritable bowel syndrome (IBS) and chronic constipation (CC) are common functional gastrointestinal disorders affecting 14% and 20% of the U.S. population, respectively. Reviews of the evidence on the burden of illness associated with IBS and CC have not been comprehensive in scope and have not provided an assessment of the distribution of health care costs across categories of resource use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
154
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 46 publications
5
154
0
3
Order By: Relevance
“…Our findings are found to be similar among medical students and interns of King Abdulaziz University in Jeddah. Moreover, they are in agreement with Korean medical students [15] [3]. In contrast, Basandra et al (2014) found that there are significant associations between IBS and the consumption of fatty food among medical students from Northern India [22].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our findings are found to be similar among medical students and interns of King Abdulaziz University in Jeddah. Moreover, they are in agreement with Korean medical students [15] [3]. In contrast, Basandra et al (2014) found that there are significant associations between IBS and the consumption of fatty food among medical students from Northern India [22].…”
Section: Discussionsupporting
confidence: 68%
“…The burden of IBS is significant enough to contribute to a considerable impairment in quality of life by affecting the person's social and emotional functioning leading to depression, decrease academic achievement and increase rate of absences from schools and work stations [15].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 It affects daily life especially in those with abdominal symptoms 21 and resulted in 13.7 million days of restricted activity; missing work or school in 12% and impaired ability to work in 60% of patients. 20 In the United States, the direct expenditure per-patient for constipation which includes medications, hospitalizations, out-patient services, emergency visits, and laboratory tests ranged from $1912 to $7522 per year 19 and increased several-fold between 1997 and 2010. 22 Moreover, a study revealed that up to 50% of chronic constipation and IBS patients use alternative or non-prescription medications, especially by women and patients with higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Reported rates of co-morbid anxiety and depression in IBS range between 30 to 60%, depending on type of health care setting and country of origin (Drossman et al, 1999;Kabra & Nadkarni, 2013). IBS has significant financial and humanistic burdens (Nellesen, Yee, Chawla, Lewis, & Carson, 2013;Spiller et al, 2007) and treatment relies on lifestyle advice, and medical and psychological therapies (Akehurst & Kaltenthaler, 2001;Talley, Holtmann, & Walker, 2015).…”
Section: Introductionmentioning
confidence: 99%